DETERMINATION OF MERCHANDISE TURNOVER. - Carson, A. B. (The Accounting Review, 1944)
Abstract The article presents information on merchandise turnover and the method of computing it. Data and statements are of limited usefulness unless they are properly interpreted. To assist and facilitate interpretation, particularly of the balance sheet and income statement, various ratio and percentage analyses frequently are made a part of, or appended to, these reports. One of the most significant of these ratios to merchandising businesses is the one that shows the average number of times the inventory was replaced during a given period. It is usually called merchandise turnover or stock-turn. The customary method of computing inventory turnover is to divide the total cost of goods sold by the average value of goods on hand during the period. It is recognized that the turnover figure obtained by the use of the suggested procedure is subject to the same weakness as that secured by the conventional method, in that it will be distorted somewhat if the period under review has been one that included sizable price changes.